HUMAN FORMATION FROM AN INTEGRAL PERSPECTIVE: DIALOGUES BETWEEN SPIRITUALITY, ETHICS, AND MORALITY IN PSYCHOLOGY - de Gerone, Lucas Guilherme Tetzlaff; Francelino, Ricardo; de Aquino, Rafael Santos; Cremasco, Ana Júlia Barbosa (Seven Editora, 2025)
Spirituality, ethics, and morality have increasingly gained prominence as interpretative keys for understanding human development and rethinking integral education in educational contexts. This chapter aims to examine, from a psychological perspective, how spirituality, morality, and ethics are articulated and how they can underpin projects of integral education oriented toward humanization, the critical exercise of consciousness, and openness to transcendence. It begins with a conceptual clarification in which spirituality is understood as the search for meaning and self-transcendence, morality as a system of sociocultural norms and practices, and ethics as critical reflection on human action, highlighting its structuring role in the constitution of subjectivity. Subsequently, a theoretical-reflective literature review with a qualitative approach is developed, encompassing different psychological traditions: Viktor Frankl’s Logotherapy; contributions from Humanistic and Transpersonal Psychology; existential and phenomenological approaches; the Psychology of Religion; psychoanalytic contributions; cultural and systemic perspectives; Positive Psychology and neuroscientific investigations of spirituality; studies in moral and developmental psychology; Historical-Cultural Psychology; and Liberation Psychology. The analysis indicates that, despite being grounded in diverse epistemological matrices, these approaches converge in recognizing spirituality as a dimension that organizes the experience of meaning, guides moral judgment, and qualifies ethical action, transcending the confessional sphere and assuming psychological, pedagogical, and social relevance. Finally, it is argued that integrating spirituality, ethics, and morality into integral education— in dialogue with Ken Wilber’s Integral Psychology and with proposals that incorporate spiritual resources and practices—fosters self-knowledge, the cultivation of values, and the capacity to attribute meaning to existence, contributing to the formation of more critical, responsible, and internally integrated subjects.DOI: https://doi.org/10.56238/sevened2025.041-001